Integration of microRNA and mRNA analyses depicts the potential roles of Momordica charantia saponin administration in insulin resistance of juvenile common carp (Cyprinus carpio) fed with a high-starch diet - Fan, Ze; Wang, Liansheng; Li, Chenhui; Wu, Di; Li, Jinnan; Zhang, Haitao; Xiong, Siwei; Miao, Linghong; Ge, Xianping; Li, Zhengwei (Frontiers in Molecular Biosciences, 2023)
Background: The regulation of target gene mRNA mediated by microRNA may play an important role in glucose metabolism in fish. Previous research findings of our research group revealed that Momordica charantia saponin (MS) administration in a high-starch diet could improve insulin resistance of common carp through renovating insulin signaling pathways, whose fundamental mechanisms have remained unknown by far. To reveal this potential mechanism, we aimed to investigate the difference in miRNA and mRNA expression profiles between common carp fed with high-starch diets containing MS (HS_MS1 and HS_MS2) and common carp fed with high-starch (HS) diets. Results: Through miRNA deep-sequencing, 10 significantly differentially expressed miRNAs in HC and HS_MS1, including one upregulated and nine downregulated miRNAs, were identified, whereas 10 significantly differentially expressed miRNAs in HC and HS_MS2, including four upregulated and six downregulated miRNAs, were identified. These miRNAs may not only be involved in the regulation of insulin signaling pathways and insulin resistance in common carp but also be the markers for liver insulin resistance in MS therapy for the remission of insulin resistance. This study identified 10 potential known miRNAs, namely, ccr-miR-10b, ccr-miR-122, ccr-miR-143, ccr-miR-146a, ccr-miR-155, ccr-miR-16c, ccr-miR-200a, ccr-miR-29a, ccr-miR-34, and ccr-miR-375, as candidates participating in modulating the liver insulin resistance. According to the biopathway enrichment analysis of the 252 target genes using the KEGG classical biopathway database, the relative expression levels of gsk3bb, pik3r1, and pik3r3b were analyzed using RNA-seq. Compared to the HC group, a significant decrease in the relative expression levels of pik3r1 and pik3r3b was observed in HS_MS1 and HS_MS2 groups (p < 0.05). This study raised a presumption of the presence of ccr-miR-29a targeting pik3r1 or ccr-miR-143 targeting pik3r3 playing likely roles in Momordica charantia saponins remitting the liver insulin resistance. Conclusion: The findings will further deepen the understanding of the carbohydrate metabolism of common carp and provide an important scientific basis for the application of Momordica saponins as functional nutrients to alleviate insulin resistance of fish in fish culture.